' Analysis of the Role of Motivation and Creativity in Local Startups to Encourage Entrepreneurial Success - Elis Anita Farida; Fitria Amelyawati; Akhmad Aziz Setia Hadi; Rizma Maulidia Putri (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the role of motivation and creativity as psychological factors that drive entrepreneurial success in local startups. Using a mixed methods approach, this study combines a quantitative survey of 50 startup founders and in-depth interviews with 10 informants in Sidoarjo. The results show that intrinsic motivation, such as the desire to achieve financial freedom and create social impact, has a stronger influence than extrinsic motivation in maintaining long-term commitment. Creativity, on the other hand, allows entrepreneurs to identify new opportunities, develop innovative solutions, and overcome operational challenges, especially in conditions of limited resources. The interaction between motivation and creativity creates significant synergy, where motivation triggers energy for creative thinking, and creativity strengthens motivation through a sense of achievement and pride. In addition, supporting factors such as environmental support, access to resources, and organizational culture that encourages innovation also play an important role in maintaining entrepreneurial motivation and creativity. Theoretically, these findings enrich the entrepreneurship literature by emphasizing the importance of the interaction between psychological factors and the external environment. Practically, this study provides recommendations for entrepreneurs to focus on developing intrinsic motivation and creativity, and for policymakers to provide resource support and training to create an inclusive and sustainable startup ecosystem.